Temporal gene profiling of the 5XFAD transgenic mouse model highlights the importance of microglial activation in Alzheimer’s disease - Landel, Véréna (Mol Neurodegener, 2014)
BACKGROUND: The 5XFAD early onset mouse model of Alzheimer’s disease (AD) is gaining momentum. Behavioral, electrophysiological and anatomical studies have identified age-dependent alterations that can be reminiscent of human AD. However, transcriptional changes during disease progression have not yet been investigated. To this end, we carried out a transcriptomic analysis on RNAs from the neocortex and the hippocampus of 5XFAD female mice at the ages of one, four, six and nine months (M1, M4, M6, M9). RESULTS: Our results show a clear shift in gene expression patterns between M1 and M4. At M1, 5XFAD animals exhibit region-specific variations in gene expression patterns whereas M4 to M9 mice share a larger proportion of differentially expressed genes (DEGs) that are common to both regions. Analysis of DEGs from M4 to M9 underlines the predominance of inflammatory and immune processes in this AD mouse model. The rise in inflammation, sustained by the overexpression of genes from the complement and integrin families, is accompanied by an increased expression of transcripts involved in the NADPH oxidase complex, phagocytic processes and IFN-γ related pathways. CONCLUSIONS: Overall, our data suggest that, from M4 to M9, sustained microglial activation becomes the predominant feature and point out that both detrimental and neuroprotective mechanisms appear to be at play in this model. Furthermore, our study identifies a number of genes already known to be altered in human AD, thus confirming the use of the 5XFAD strain as a valid model for understanding AD pathogenesis and for screening potential therapeutic molecules.